2016
DOI: 10.1038/nature19847
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome conformation elucidates regulatory relationships in developing human brain

Abstract: Three-dimensional physical interactions within chromosomes dynamically regulate gene expression in a tissue-specific manner1–3. However, the 3D organization of chromosomes during human brain development and its role in regulating gene networks dysregulated in neurodevelopmental disorders, such as autism or schizophrenia4–6, are unknown. Here we generate high-resolution 3D maps of chromatin contacts during human corticogenesis, permitting large-scale annotation of previously uncharacterized regulatory relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
712
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(754 citation statements)
references
References 46 publications
41
712
1
Order By: Relevance
“…New initiatives such as CommonMind and PsychENCODE are providing data and tools for the neuro-psychiatry research community to follow up on GWAS signals. New analytical methods now provide the first steps of functional in silico follow-up by exploiting the availability of resource datasets detailing gene expression, epigenetic marks, 3D chromatin contacts, 71 or other genomic annotations, including drug targets. One fertile area of method development is integrating data from GWASs and expression quantitative trait locus (eQTL) studies to identify associations between transcripts and complex traits.…”
Section: From Gwas To Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…New initiatives such as CommonMind and PsychENCODE are providing data and tools for the neuro-psychiatry research community to follow up on GWAS signals. New analytical methods now provide the first steps of functional in silico follow-up by exploiting the availability of resource datasets detailing gene expression, epigenetic marks, 3D chromatin contacts, 71 or other genomic annotations, including drug targets. One fertile area of method development is integrating data from GWASs and expression quantitative trait locus (eQTL) studies to identify associations between transcripts and complex traits.…”
Section: From Gwas To Biologymentioning
confidence: 99%
“…Functional follow-up is necessarily more difficult for psychiatric disorders, and to date, bioinformatic analyses have been the key focus providing strategies for prioritization of loci. Schizophrenia risk loci are over-represented in regulatory regions active in the brain 15,130,131 and are enriched in genes from postsynaptic density, postsynaptic membrane, dendritic spine, axon, and voltage-gated potassium channel pathways, as well as histone H3-K4 methylation 132 71 Fine-mapping has been accomplished for the strongest, and first identified, association with schizophrenia in the MHC region, a challenge because of its high genic content and high LD. The position of the association signal within the MHC region led to investigation of common structural haplotypes of complement factor 4 genes C4A (MIM: 120810) and C4B (MIM: 120820), combinations of which correlated well with schizophrenia risk and increased C4 expression and showed differential brain expression between case and control individuals.…”
Section: Schizophreniamentioning
confidence: 99%
“…For example, the obesity-associated FTO variant (rs1421085) was found to disrupt an ARID5B repressor motif in an enhancer for IRX3/5 during adipocyte differentiation, increasing obesity risk [10]. A second study showed a schizophrenia-associated SNP (rs1191551) regulates the expression of distal gene FOXG1 in two zones of the developing human cerebral cortex, rather than targeting the nearby gene PRKD1 [13]. Another example is a papillary thyroid cancer associated SNP (rs965513) in an LD block containing several enhancer variants that contact the promoter of FOXE1 and alter its expression [18].…”
mentioning
confidence: 99%
“…Large-scale endeavors such as ENCODE 61 and the Roadmap Epigenome Consortium (REC) 62 have created a reference for human epigenome annotation. Parallel efforts focused on brain tissue, such as the PsychENCODE Consortium 63 , will help extend these resources 64 . Cataloguing human variation: Building a database of human variation has proven invaluable in interpreting the coding genome 65 and the Genome Aggregation Database (gnomAD, http://gnomad.broadinstitute.org) extends this approach to WGS.…”
Section: Identifying Functional Variantsmentioning
confidence: 99%